THE EFFECT OF DISCOVERY LEARNING IMPLEMENTATION ON SCIENCE LITERATURE ABILITY REVIEWING FROM SELF REGULATION LEARNING ELEMENTARY SCHOOL STU-DENTS - Putri Lestari, Nyoman Ayu; Dewi, Made Sri Astika (JURNAL PENDIDIKAN DASAR NUSANTARA, 2022)
Abstract: This study aims to determine the effect of Discovery Learning model on scientific literacy skills in terms of Self Regulation Learning in class V Cluster II students, Jembrana District. The research design is 2x2 factorial experimental design. The number of population members is 137 students, and number of sample members is 116 students drawn by random sampling. Science literacy ability data was collected by multiple choice test and Self Regulation Learning data was collected by questionnaire. Analysis of the data used in this study was two-way ANOVA and t-Scheffe test assisted by SPSS 17.0 for windows. The results of study showed 1) there are differences in scientific literacy skills between students who follow the Discovery Learning model and students who follow the conventional model 2) there is an interaction effect between the learning model and Self Regulation Learning 3) there are differences in scientific literacy skills between students who follow the Discovery Learning model and students who follow the conventional model of students who have high Self Regulation Learning 4) there are differences in scientific literacy skills between students who follow the Discovery Learning model and students who follow the conventional model of students who have low Self Regulation Learning. Keywords: discovery learning, literacy skills, self-regulation learning.